Efficient Radical‐Enhanced Intersystem Crossing in an NDI‐TEMPO Dyad: Photophysics, Electron Spin Polarization, and Application in Photodynamic Therapy. Issue 70 (4th December 2018) - Wang, Zhijia; Gao, Yuting; Hussain, Mushraf; Kundu, Sushma; Rane, Vinayak; Hayvali, Mustafa; Yildiz, Elif Akhüseyin; Zhao, Jianzhang; Yaglioglu, Halime Gul; Das, Ranjan; Luo, Liang; Li, Jianfeng
Abstract: A compact naphthalenediimide (NDI)–2, 2, 6, 6‐tetramethylpiperidinyloxy (TEMPO) dyad has been prepared with the aim of studying radical‐enhanced intersystem crossing (EISC) and the formation of high spin states as well as electron spin polarization (ESP) dynamics. Compared with the previously reported radical–chromophore dyads, the present system shows a very high triplet state quantum yield ( Φ T =74 %), a long‐lived triplet state ( τ T =8.7 μs), fast EISC (1/ k EISC =338 ps), and absorption in the red spectral region. Time‐resolved electron paramagnetic resonance (TREPR) spectroscopy showed that, upon photoexcitation in fluid solution at room temperature, the D0 state of the TEMPO moiety produces strong emissive ( E ) polarization owing to the quenching of the excited singlet state of NDI by the radical moiety (electron exchange J >0). The emissive polarization then inverts into absorptive ( A ) polarization within about 3 μs, and then relaxes to a thermal equilibrium while quenching the triplet state of NDI. The formation and decay of the quartet state were also observed. The dyad was used as a three‐spin triplet photosensitizer for triplet–triplet annihilation upconversion (quantum yield Φ UC =2.6 %). Remarkably, when encapsulated into liposomes, the red‐light‐absorbing dyad–liposomes show good biocompatibility and excellent photodynamic therapy efficiency (phototoxicity EC50 =3.22 μm ), and therefore is a promising candidate for future less toxic and multifunctional photodynamic therapeutic reagents. Abstract : The future for photodynamic therapy? The stable radical–visible‐light‐harvesting chromophore dyadNDI‐TEMPO (naphthalenediimide–2, 2, 6, 6‐tetramethylpiperidinyloxy) shows highly efficient radical‐enhanced intersystem crossing (74 %), a long‐lived triplet state of NDI (8.7 μs), quartet state formation ( S =3/2), inversion of electron spin polarization (ESP), high triplet–triplet annihilation upconversion quantum yield (2.6 %), and efficient photodynamic therapy (PDT, see figure). These results are useful for the future design of heavy‐atom‐free triplet photosensitizers and less toxic and multifunctional PDT reagents.